Regulation of neuronal high-voltage activated CaV2 Ca2+ channels by the small GTPase RhoA. (October 2015) - Rousset, Matthieu; Cens, Thierry; Menard, Claudine; Bowerman, Melissa; Bellis, Michel; Brusés, Juan; Raoul, Cedric; Scamps, Frédérique; Charnet, Pierre
Abstract: High-Voltage-Activated (HVA) Ca 2+ channels are known regulators of synapse formation and transmission and play fundamental roles in neuronal pathophysiology. Small GTPases of Rho and RGK families, via their action on both cytoskeleton and Ca 2+ channels are key molecules for these processes. While the effects of RGK GTPases on neuronal HVA Ca 2+ channels have been widely studied, the effects of RhoA on the HVA channels remains however elusive. Using heterologous expression in Xenopus laevis oocytes, we show that RhoA activity reduces Ba 2+ currents through CaV 2.1, CaV 2.2 and CaV 2.3 Ca 2+ channels independently of CaV β subunit. This inhibition occurs independently of RGKs activity and without modification of biophysical properties and global level of expression of the channel subunit. Instead, we observed a marked decrease in the number of active channels at the plasma membrane. Pharmacological and expression studies suggest that channel expression at the plasma membrane is impaired via a ROCK-sensitive pathway. Expression of constitutively active RhoA in primary culture of spinal motoneurons also drastically reduced HVA Ca 2+ current amplitude. Altogether our data revealed that HVA Ca 2+ channels regulation by RhoA might govern synaptic transmission during development and potentially contribute to pathophysiological processes when axon regeneration and growth cone kinetics are impaired. Highlights: Regulation of voltage-gated Ca 2+ channels by RHoa was analyzed. RhoA was co-expressed in Xenopus oocyte with CaV 2.1, CaV 2.2 or CaV 2.3 Ca 2+ channels. RhoA suppressed all CaV 2.x -induced Ca 2+ currents. The decrease in the number of active channels was due to activation of ROCK. Over-expressed RhoA also suppressed Ca 2+ currents in motoneurons.